Sturm Comparison Theorems for Half-Linear Equations with a Damping Term - Oinarov, Ryskul; Ramazanova, Khanym; Tiryaki, Aydin (Eurasian Mathematical Journal, 2015)
In this paper, first we establish a Picone-type inequality for a pair of half-linear equations with a damping term. Next we prove some Sturm-type comparison theorems via the Picone-type inequality.